2009
DOI: 10.1111/j.1399-5448.2008.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of novel dual wave meal bolus and its impact on glycated hemoglobin A1c level in children with type 1 diabetes

Abstract: Patients using at least one D-W/S-W bolus per day achieved a recommended level of HbA1c. Paediatric patients with type 1 diabetes mellitus were found to be able to apply D-W/S-W boluses in daily self-treatment process based on food counting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 13 publications
3
83
0
4
Order By: Relevance
“…Chase et al 12) first described the efficacy of a dualwave bolus in handling postprandial glycemia compared with the other insulin delivery methods on pump therapy in patients with T1DM. Pańkowska et al 15) proposed the fat-protein exchange unit (FPU) to accompany carbohydrate exchanges in calculating the correct prandial insulin dose. Taking the protein-fat content of the meal into consideration with the FPU would lead to use of biphasic supply of insulin wave on basal-bolus regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chase et al 12) first described the efficacy of a dualwave bolus in handling postprandial glycemia compared with the other insulin delivery methods on pump therapy in patients with T1DM. Pańkowska et al 15) proposed the fat-protein exchange unit (FPU) to accompany carbohydrate exchanges in calculating the correct prandial insulin dose. Taking the protein-fat content of the meal into consideration with the FPU would lead to use of biphasic supply of insulin wave on basal-bolus regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new insulin delivery method is needed in taking a protein-and fat-rich meal. Several studies [12][13][14][15][16] have demonstrated insulin delivery using a dual-wave bolus on pump therapy is better to control postprandial glycemia after taking protein-and fat-rich meals. Chase et al 12) first described the efficacy of a dualwave bolus in handling postprandial glycemia compared with the other insulin delivery methods on pump therapy in patients with T1DM.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Çalışmaların çoğunda, pompa tedavisi uygulanan Tip 1 diyabetlilerde yük-sek yağ ve/veya protein içeren öğünler için en etkili bolus şeklinin çift dalga bolus olduğu ifade edilmektedir. [42][43][44][45] Chase ve ark.nın yaptığı çalış-mada, yağlı pizza ve tiramisu öğünü için en iyi postprandiyal glisemiyi çift dalga bolus uygulamasının sağladığı saptanmıştır. 42 Benzer şekilde Jones ve ark.…”
Section: Di̇yet Yağ Ve Protei̇nleri̇ İçi̇n İnsüli̇n Bolus Dozu Bolus Zamaunclassified
“…Karbonhidrat içeriğine göre standart bolus, y-p ünitesine göre de kare dalga bolus uygulaması yapılmaktadır. 45 Pańkowska'nın algoritması kullanılan iki klinik çalış-mada, çift dalga bolus uygulaması ve karbonhidrat sayımına ek olarak y-p sayımının daha iyi glisemik kontrol sağladığı, postprandiyal glukoz seviyelerini düşürdüğü bildirilmiştir. Ancak, karbonhidrat sayımıyla karşılaştırıldığında bu metodun klinik olarak önemli derecede hipoglisemiye neden olduğu ifade edilmektedir.…”
Section: Di̇yet Yağ Ve Protei̇nleri̇ İçi̇n İnsüli̇n Bolus Dozu Bolus Zamaunclassified
“…In the study of Pańkowska et al, in which metabolic control was evaluated in a group of 499 pediatric patients treated with the use of PIP, and on the basis of analysis of the data from 2-week reports of reading the data from insulin pumps, it was demonstrated that patients using square and dual-wave boluses in the amount of two or more per day achieve a lower percentage of glycosylated hemoglobin compared to those who use these types of boluses less frequently than once a day [56]. However, the composition of different meals where the above types of boluses were adiministered was not analysed, but the focus was placed on an assessment of the degree of use of the technical possibilities offered by this method of treatment.…”
Section: Protein and Fat Exchangesmentioning
confidence: 99%